2023
DOI: 10.1007/s13143-023-00324-6
|View full text |Cite
|
Sign up to set email alerts
|

Intra-urban Variations of the CO2 Fluxes at the Surface-Atmosphere Interface in the Seoul Metropolitan Area

Abstract: Severe spatiotemporal heterogeneity of emissions sources and limited measurement networks have been hampering the monitoring and understanding of CO2 fluxes in large cities, a great concern in climate research as big cities are among the major sources of anthropogenic CO2 in the climate system. To understand the CO2 fluxes in Seoul, Korea, CO2 fluxes at eight surface energy balance sites, six urban (vegetation-area fraction < 15%) and two suburban (vegetation-area fraction > 60%), for 2017–2018 are analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Conversely, there were fewer areas where the annual CO2 flux values increased, and these were more scattered, primarily located in the eastern part of Haiwan Town, with a growth rate of up to 6.74%. Combined with the land use changes in Fengxian District of Shanghai, it was found that the areas with decreased CO2 flux values generally corresponded to regions with denser vegetation, while areas with increased CO2 flux values were associated with increased land for construction purposes [40].…”
Section: Interannual Variation Of Co2 Flux Spatial Distributionmentioning
confidence: 99%
“…Conversely, there were fewer areas where the annual CO2 flux values increased, and these were more scattered, primarily located in the eastern part of Haiwan Town, with a growth rate of up to 6.74%. Combined with the land use changes in Fengxian District of Shanghai, it was found that the areas with decreased CO2 flux values generally corresponded to regions with denser vegetation, while areas with increased CO2 flux values were associated with increased land for construction purposes [40].…”
Section: Interannual Variation Of Co2 Flux Spatial Distributionmentioning
confidence: 99%